1987
DOI: 10.1002/bms.1200140506
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and quantification of biogenic amines in wine by constant B2E linked scan mass spectrometry

Abstract: The constant B2E linked scan is shown to be an excellent tool for the profiling of biogenic amines in wine samples. The fragment ion at m/z 169 of the dansylated amines is used for the precursor ion search in combination with direct sample evaporation. Besides the profile a semi-quantification may be achieved when using suitable amines as internal standards with standard deviations of 12-17%. More accurate results with standard deviations of 3-5% are obtained when using deuterated analogues as internal standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…MSMS was performed in the positive as well as negative ion mode. In the positive FAB mode, major fragment ions for Dns-Gro-Cys at m/z 170 and 171 due to the (dimethylamino)naphthalene group were observed (Addeo et al, 1975;Walther et al, 1987) (our data not shown). The dansylated compounds gave stronger quasimolecular signal intensities in the negative ion mode, and this is exemplified by the negative ion FAB-MS of Dns-Gro-Cys shown in Figure 4.…”
Section: Resultsmentioning
confidence: 68%
“…MSMS was performed in the positive as well as negative ion mode. In the positive FAB mode, major fragment ions for Dns-Gro-Cys at m/z 170 and 171 due to the (dimethylamino)naphthalene group were observed (Addeo et al, 1975;Walther et al, 1987) (our data not shown). The dansylated compounds gave stronger quasimolecular signal intensities in the negative ion mode, and this is exemplified by the negative ion FAB-MS of Dns-Gro-Cys shown in Figure 4.…”
Section: Resultsmentioning
confidence: 68%
“…4A, insert). This peak is flanked by ions at m/z 169 and 171, which are described as being characteristic of dansylated amines (Walter et al 1987). In addition to this major peak, other peaks are observed at m/z 321, 304, 234, and 220.…”
Section: Structural Identification Of Putrescine As a Root Exudate Co...mentioning
confidence: 89%
“…In a second type of experiment a product ion may be selected and all precursor ions determined. This approach allows the investigator to define homologous families or classes of compounds, e. g. terpenes in oil shale (63), biogenic amines in wine (64), and sulfated azo dyes in regulated products (65). In the third strategy, the two mass spectrometers are scanned in parallel to permit detection of all decompositions that proceed with elimination of neutral fragments of a predetermined mass.…”
Section: Scanning Strategiesmentioning
confidence: 99%